2021
DOI: 10.1007/s00066-021-01773-6
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous stereotactic radiosurgery of multiple brain metastases using single-isocenter dynamic conformal arc therapy: a prospective monocentric registry trial

Abstract: Background Single-isocenter dynamic conformal arc (SIDCA) therapy is a technically efficient way of delivering stereotactic radiosurgery (SRS) to multiple metastases simultaneously. This study reports on the safety and feasibility of linear accelerator (LINAC) based SRS with SIDCA for patients with multiple brain metastases. Methods All patients who received SRS with this technique between November 2017 and June 2019 within a prospective registry trial wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Bodensohn, et. al reported on the feasibility and safety of single isocenter treatments for patients with multiple brain metastases [ 7 ]. In the view of the newly proposed legislation by the Centers for Medicare & Medicaid Services (CMS) on an Alternative Payment Model (APM) affecting Radiation Oncology, the single isocenter treatment technique is a timely and relevant treatment method considering the upcoming bundled reimbursement rates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bodensohn, et. al reported on the feasibility and safety of single isocenter treatments for patients with multiple brain metastases [ 7 ]. In the view of the newly proposed legislation by the Centers for Medicare & Medicaid Services (CMS) on an Alternative Payment Model (APM) affecting Radiation Oncology, the single isocenter treatment technique is a timely and relevant treatment method considering the upcoming bundled reimbursement rates [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the platforms that treat MIM with a single isocentre, poor isocentre placement can lead to compromised coverage during treatment, particularly without the use of 6 dof corrections and intrafraction monitoring systems. 67,91,92 Gamma Knife and linac-based CC platforms are immune to this issue as the isocentre is individually placed inside each target and CyberKnife treatments are non-isocentric. For these platforms, large numbers of mets can take considerable time to deliver (CyberKnife utilises about 10 times more MU than Elements DCA to deliver the same prescription).…”
Section: Discussion Of Clinical Cases and Clinical Evaluation Of Mim Treatment Platforms And Tpsmentioning
confidence: 99%
“…While this approach may not be ideal for complex targets, the geometric simplicity of intracranial metastases makes this solution quite attractive. 67 The low degree of MLC modulation lends itself to simpler dosimetry, faster delivery and monitor unit economy. The use of the linac’s primary and secondary collimators for SRS increases the field size and therefore target size that can be treated, allowing for the first time the simultaneous treatment of multiple targets via the same arc.…”
Section: Mim Platforms and Treatment Planning Systems Utilized In This Studymentioning
confidence: 99%
“…Whole brain radiation therapy (WBRT) is the most widely used treatment for patients with disseminated brain metastases and bulky meningeal disease [7,8]. Bodensohn et al demonstrated that a simultaneous stereotactic radiosurgery using a single-isocenter dynamic conformal arc (SIDCA) seems to be a feasible and safe treatment for patients with multiple brain metastases [9]. However, WBRT is the conventional treatment for patients with LM and provides attenuation of prevalent neurological signs and symptoms [10].…”
Section: Introductionmentioning
confidence: 99%